Establishment of the European Medical Students' Neurosurgery Society–A Proposal. Issue 5 (23rd March 2019) - Stumpo, Vittorio
Abstract: INTRODUCTION: Recent years have witnessed the birth in the United States of Neurosurgery Medical Students Chapters aimed at fostering the interest toward neurosurgery and at supporting students willing to pursue a career in academic neurosurgery by making available research and mentoring opportunities. The American Association of Neurological Surgeons has pioneered the support of these programs and medical chapters are currently active in most US medical schools where they receive support from local Neurosurgery Departments and Research Centers. On the contrary, the European network of medical students' neurosurgical interest groups is fragmented and this opportunity is largely unexploited. METHODS: The present abstract is intended to propose the establishment of the European Medical Students' Neurosurgery Society which would represent a tremendous opportunity to build a collaborative network and promote students' interest toward neurosurgery with the aim of increasing learning, research and mentoring opportunities. RESULTS: The Italian Medical Student Neurosurgery Interest Group is currently underway and will be launched soon. Other medical students' societies active in European countries are invited to join this project to establish a proactive European Neurosurgical Student Network and to advocate the birth of other groups. CONCLUSION: The establishment of this society under EANS support would represent the ideal platform for leadership positions in the medical student community at local and national level that will be important to acquire experience and promote a virtuous circle of knowledge and service while also providing the basis for scientific production on the current state of medical students' recruiting in neurosurgery around Europe.